Stroma‐and Tumor‐Associated Predictive Features in Salivary Gland Adenoid Cystic Carcinoma of the Head and Neck - Rytkönen, Aleksi; Laine, Hanna K.; Mäkitie, Antti; Haglund, Caj; Hagström, Jaana; Almangush, Alhadi; Leivo, Ilmo (Wiley, 2025)
Background: There is lack of knowledge on the utility of prognostic histopathologic characteristics in adenoid cysticcarcinoma (ACC) of the head and neck. We evaluated the prognostic value of tumor and stroma-related histopathologicfeatures in ACC.
Materials and Methods: A total of 65 cases of ACC from minor and major salivary glands were included in this study. Weevaluated tumor budding, tumor-infiltrating lymphocytes (TILs), and tumor-stroma ratio (TSR) in hematoxylin and eosin (HE)stained sections.
Results: Stroma-rich ACCs recurred more frequently (p = 0.029) during follow-up and associated with distant metastasis(p = 0.038). In multivariable analysis, stroma-rich tumors associated with poorer disease-specific survival with a hazardratio of 3.76 (95% CI 1.10–12.83, p = 0.034). ACCs commonly showed a low infiltration of TILs as 89% of the tumors wascharacterized by an immune desert pattern. Low infiltration of TILs associated significantly with increased tumor budding(p = 0.039).
Conclusion: Adverse features of TSR and tumor budding are widely expressed in ACC, and stroma-rich tumors are associatedwith poor prognosis. Low number of TILs in ACC tissue indicates a weak immune response by the host and illustrates the natureof ACC as a relentless malignancy.